Coral plant (Jatropha multifida L) leaf extracts inhibit dengue virus-2 (DENV-2) growth through NS5 - Yuniyanti, Mia Munawaroh; Sri Hartati Wahyuningsih, Mae (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
The incidence of dengue fever (DF) increases drastically from year to year, especially in tropical countries like Indonesia. In contrast, antiviral against dengue virus (DENV) is not available in clinics, yet. Jatropha multifica L, locally named tanaman yodium/coral plant, is a medicinal plant that is traditionally used to treat dengue hemorrhagic fever (DHF). However, its scientific evidence is limited. This study aimed to investigate the antiviral activity of J. multifida L leaf extracts against DENV-2 and evaluate the effect on NS5 RNA expression. The leaf extracts were prepared by multilevel extraction using chloroform and methanol. The study was conducted in vitro using DEN-2 and Vero cells. The antiviral activity was assessed by using qRT-PCR to assess the number of virus copies and then used to calculate the inhibitory concentration of 50% (IC50). The effect of the most active extract on NS5 DENV-2 RNA expression was then evaluated by using qRT-PCR. Among 4 extracts tested, the methanolic insoluble chloroformic extract (MIS) is the most active with an IC50 value of 124.3 μg/mL. Furthermore, the MIS (0.02) strongly inhibited NS5 DENV-2 RNA expression compared to control (1.0). In conclusion, the MIS of J. multifida is active against DENV-2 through inhibition of NS5 RNA expression.